2010
DOI: 10.1021/ja102264w
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-17 Appears Only in Protein in Water-Stressed Soybean Leaves Labeled by 17O2

Abstract: We have used a rotational-echo adiabatic-passage double-resonance (13)C{(17)O} solid-state NMR experiment to prove that the glycine produced in the oxygenase reaction of ribulose bisphosphate carboxylase-oxygenase is incorporated exclusively into protein (or protein precursors) of intact, water-stressed soybean leaves exposed to (13)CO(2) and (17)O(2). The water stress increased stomatal resistance and decreased gas exchange so that the Calvin cycle in the leaf chloroplasts was no more than 35% (13)C isotopica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…a, top left and right). This is the same conclusion that was reached earlier by using 17 O 2 labeling of the C 2 pathway in a water‐stressed whole soybean leaf with NMR detection of 17 O label only in protein, and not in starch or sugars (Gullion et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…a, top left and right). This is the same conclusion that was reached earlier by using 17 O 2 labeling of the C 2 pathway in a water‐stressed whole soybean leaf with NMR detection of 17 O label only in protein, and not in starch or sugars (Gullion et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Using solid‐state nuclear magnetic resonance (NMR), we have found that a fraction of the glycine from the photorespiratory C 2 cycle is not decarboxylated or returned to the Calvin cycle (Noctor et al ., ), but is inserted instead as glycyl residues in proteins (Cegelski & Schaefer, ; Gullion et al ., ). This result is consistent with earlier experiments using 14 CO 2 labeling and detection of label in both amino acids and proteins (Ongun & Stocking, ; Dickson & Larson, ).…”
Section: Introductionmentioning
confidence: 97%
“…Other very similar studies taking advantage of 17 O– 13 C (Guillon et al ., ) or other hetero–nuclear interactions (Cegelski & Schaefer, ) and NMR technology have also suggested that under low CO 2 or water stress, glycine is not converted to phosphoglycerate and is instead incorporated into proteins. These studies are probably flawed as they have no consideration for 13 C enrichment in Ser C‐1 or C‐2; neglect 17 O/ 16 O exchange with solvent water (e.g.…”
Section: Do Photorespiratory Reactions Form a Closed Cycle?mentioning
confidence: 99%
“…In an extreme case, a 13 C-17 O REDOR experiment on soybean leaves required several months of NMR time. [3] In order to obtain quantitative results from NMR experiments taking a long time, the parameters of the experiment must be accurately controlled. Precise sample spinning speeds are necessary for rotor-synchronized pulse trains, [4] and most laboratories are equipped with good spinning speed controllers.…”
Section: Introductionmentioning
confidence: 99%
“…Magic angle sample spinning NMR experiments can last days and, possibly, weeks. In an extreme case, a 13 C– 17 O REDOR experiment on soybean leaves required several months of NMR time . In order to obtain quantitative results from NMR experiments taking a long time, the parameters of the experiment must be accurately controlled.…”
Section: Introductionmentioning
confidence: 99%